2011
DOI: 10.1016/j.atherosclerosis.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic epidemiology of homozygous familial hypercholesterolemia in the Hokuriku district of Japan

Abstract: Methods: Twenty-five homo-FH patients were recruited. LDLR mutations were identified using the Invader assay method. Mutations in PCSK9 were detected by PCR-SSCP followed by direct sequence analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 11 publications
2
75
1
1
Order By: Relevance
“…In 2011, Mabuchi et al reported an updated estimation of FH frequency in Japan. Based on 18 HoFH cases identified in a population of 3,081,000 in Hokuriku district and calculated using the Hardy-Weinberg equilibrium, the authors estimated that the frequencies of HoFH and HeFH were 1/171,167 (5.8 per million) and 1/208 (0.48%), respectively 25) . The estimated frequencies of HoFH and HeFH, according to this study, were much higher than the well-known estimations in Western populations.…”
Section: Frequency Of Fh In Asian Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Mabuchi et al reported an updated estimation of FH frequency in Japan. Based on 18 HoFH cases identified in a population of 3,081,000 in Hokuriku district and calculated using the Hardy-Weinberg equilibrium, the authors estimated that the frequencies of HoFH and HeFH were 1/171,167 (5.8 per million) and 1/208 (0.48%), respectively 25) . The estimated frequencies of HoFH and HeFH, according to this study, were much higher than the well-known estimations in Western populations.…”
Section: Frequency Of Fh In Asian Populationsmentioning
confidence: 99%
“…In 2012, the gene mutations for FH were identified in 130/208 patients clinically diagnosed with FH by the SBRG criteria in Taiwan, including 118 mutations in the LDLR gene and 12 in the ApoB gene 33) . In a Japanese study, 13/15 HoFH patients had LDLR gene mutations and 2/15 had PCSK9 gene mutations; among 10 HeFH patients with LDLR gene mutations, three patients also had PCSK9 gene mutations 25) . In 2014, a cohort of 1,055 HeFH patients and 41 HoFH patients was enrolled in a study in Japan 38) .…”
Section: Genotypes Of Fh Reported In Asian Populationsmentioning
confidence: 99%
“…3,5) Tendon xanthomas appear as Achilles tendon thickness (ATT) in many cases, which can be diagnosed easily based on inspection and palpation. Patients with ATT of 9 mm or more on radiography should be regarded as having tendon xanthomas.…”
Section: Prevalence Of Heterozygous Fh In Acsmentioning
confidence: 99%
“…[3][4][5][6] However, the prevalence likely represents an underestimate in most countries because of a majority of patients with FH are undiagnosed. 4,7) The risk of premature coronary artery disease (CAD) is elevated to about 20-fold in heterozygous FH.…”
mentioning
confidence: 99%
See 1 more Smart Citation